Rapid and highly sensitive analysis of ethoxyquin residues in shrimp using ultra performance liquid chromatography-tandem mass spectrometry - Songkran Chikakul (Chulalongkorn University, 2013)
Thesis (M.Sc.)--Chulalongkorn University, 2011